The Concept of Islamic Education and Communicative Rationality in the Thought of Ismail Raji Al-Faruqi and Jürgen Habermas - Athar Abdullatif Husain; Khoiriyah; Muhammad Alfi Syahrin (PT. Caesarindo Triloka Persada, 2026)
This study aims to analyze the crisis of public communication in Indonesia’s digital era, which is characterized by polarization, disinformation, and degrading identity labeling, while also tracing the pedagogical and ethical roots of this phenomenon. The study positions itself at the intersection of digital communication studies and Islamic education by proposing an integrative approach based on the thought of Ismail Raji Al-Faruqi and Jürgen Habermas. Using a qualitative approach through a literature study method, this research examines the concept of tawhid as an ethical-transcendental foundation and communicative rationality as a mechanism for rational dialogue in the public sphere. The analysis results in a conceptual synthesis in the form of a dialogical-tawhidi model of Islamic education that integrates the values of tawhid with procedures of rational discourse. This model is oriented toward developing learners who possess ethical awareness, critical thinking skills, and dialogical competence in responding to the dynamics of the digital public sphere. Normatively, this model may serve as a theoretical framework for the reform of Islamic education in strengthening a more inclusive and dignified culture of public communication in the digital era.